2011
DOI: 10.1371/journal.pone.0027344
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Trajectories of Chimpanzee Social Play: Similarities with Humans

Abstract: Social play, a widespread phenomenon in mammals, is a multifunctional behavior, which can have many different roles according to species, sex, age, relationship quality between playmates, group membership, context, and habitat. Play joins and cuts across a variety of disciplines leading directly to inquiries relating to individual developmental changes and species adaptation, thus the importance of comparative studies appears evident. Here, we aim at proposing a possible ontogenetic pathway of chimpanzee play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 86 publications
3
69
0
Order By: Relevance
“…This suggests that the closer in age two calves are, the more likely they are to play with each other. A similar play partner preference has been reported in other social species, including bighorn sheep (Ovis Canadensis; Hass & Jenni, 1991), sable antelope (Thompson, 1996b) vervet monkeys, (Govindarajulu et al, 1993), gorillas (Maestripieri & Ross, 2004), and chimpanzees (Cordoni & Palagi, 2011;Mendoza-Granados & Sommer, 1995).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This suggests that the closer in age two calves are, the more likely they are to play with each other. A similar play partner preference has been reported in other social species, including bighorn sheep (Ovis Canadensis; Hass & Jenni, 1991), sable antelope (Thompson, 1996b) vervet monkeys, (Govindarajulu et al, 1993), gorillas (Maestripieri & Ross, 2004), and chimpanzees (Cordoni & Palagi, 2011;Mendoza-Granados & Sommer, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, play bouts with similaraged animals were longer lasting, and the duration of play bouts decreased with an increase in age difference between partners. Such preference for play amongst like-aged partners has been demonstrated in other primates, including chimpanzees (Pan troglodytes; Cordoni & Palagi, 2011;Goodall, 1968), western lowland gorillas (Gorilla gorilla gorilla; Maestripieri & Ross, 2004), Japanese macaques (Macaca fuscata; Itani, 1954), crab-eating macaques (Macaca fascicularis; Fady, 1969), baboons (Papio anubis; Cheney, 1978;Owens, 1975), Japanese monkeys (Macaca fuscatai; Imakawa, 1990), and rhesus monkeys (Macaca mulatta; Tartabini, 1991), as well as non-primate mammals (e.g., Cuvier's gazelle, Gazella cuvieri, Gomendio, 1988;Belding's ground squirrel, Spermophilis beldingi, Holmes, 1994;bison, Bison bison, Rothstein & Griswold, 1991;sable antelope, Hippotragus niger, Thompson, 1996b).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This complexity is evident in their high fission-fusion dynamics (Campbell and Fiske 1959;Wrangham 1975) as well as in other aspects of their social dynamics such as hierarchy (Newton-Fisher 2004), sociosexual interactions (Gomes and Boesch 2009;Stumpf and Boesch 2010), mother-infant relationships (de Lathouwers and van Elsacker 2004;Hirata 2009), play behavior (Cordoni and Palagi 2011;Palagi 2007), and grooming (Nakamura 2003). Infants and juveniles learn species-typical behaviors, including foraging skills, tool use, and cultural traditions (McGrew 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be possible that this touch type also functions as a play behaviour, particularly among young individuals, but then develops into aggressive behaviour among adults. Similar behavioural changes as a consequence of maturation are observed in other species; for example, 'chase' and 'kick' behaviours in primates (Nishida et al 2010;Cordoni & Palagi 2011). There are few studies on the change in these behaviours from the development viewpoint, though Nishida (2003) revealed that in wild chimpanzees the reaction of recipients to such behaviours changes depending on the actors' age.…”
Section: Discussionmentioning
confidence: 71%